Global UX : design and research in a connected world - Quesenbery, Whitney (Morgan Kaufmann, 2012)
Protocols exist in the field of user experience, but in light of the challenges faced by globalization, you must now incorporate new methodologies and best practices to analyze, test, design, and evaluate products that take into account a multinational user base. Current UX books and resources don't focus on the unique challenges of creating usable, well-designed products and services in light of varying cultures, technology, and breadth of audience. Challenges you may face on a daily level include: Policies, practices and behavior in multinational organizations; Cross-cultural distributed team issues; Multi-national corporations working across national boundaries and across cultures (both national and corporate); Global standards and national regulations; Accessibility for a global audience, including disabilities; and much more. With Global UX, industry leaders Whitney Quesenbery and Daniel Szuc resolve this issue by offering real world examples of successful UX practice, organized by the authors around specific project objectives, as examples of different ways of working globally. Throughout the book, they provide best practices and lessons learned to help answer common questions and avoid common problems in a multitude of situations. The chapters introduce themes and frameworks of challenges, and then provide related case studies that present how experts solved that problem. This book provides a valuable resource for anyone looking to incorporate new globalized methodologies. *Covers practical user experience best practices for the global environment *Features numerous, global, real-world examples, based on interviews with over 60 UX managers and practitioners from around the world *Contains case studies and vignettes from user research and design projects for multinational companies and small start-ups.